Warak Ngendhog Commodification as a Kind of Creative Industry in Semarang City - Febriana, Kharisma Ayu; Setiawan, Yuliyanto Budi; Ersyad, Firdaus Azwar (Universitas Semarang, 2019)
Warak Ngendhog in Semarang City make it a cultural phenomenon. Some forms of commodification are used in the economic, political and cultural sectors. The purpose of this study is to find out the symptoms of the cultural phenomenon which has transformed into various forms. This research use qualitative analysis with descriptive approach. As for the results of this study, Warak Ngendhog which functions has transformed and changed, can be utilized in the cultural and tourism sectors as one of the cultural icons in the city of Semarang. Warak Ngendhog culture has contributed to the government of Semarang City with the emergence of various forms of its transformation into various forms of art and culture. In addition, this study is expected to give contribution in the field of cultural preservation in Semarang City.